2023
DOI: 10.3390/cimb45060317
|View full text |Cite
|
Sign up to set email alerts
|

How Do Cancer-Related Mutations Affect the Oligomerisation State of the p53 Tetramerisation Domain?

Abstract: Tumour suppressor p53 plays a key role in the development of cancer and has therefore been widely studied in recent decades. While it is well known that p53 is biologically active as a tetramer, the tetramerisation mechanism is still not completely understood. p53 is mutated in nearly 50% of cancers, and mutations can alter the oligomeric state of the protein, having an impact on the biological function of the protein and on cell fate decisions. Here, we describe the effects of a number of representative cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Starting from the measured D value the apparent MW of the oligomers was calculated by the combination of Stokes À Einstein equation [34,35] with the relationship between molar radius and formula weight. [33] Assuming a spherical model, dioxane molecule radius (r H diox = 0.212 nm) was used as standard to obtain estimates of the effective hydrodynamic radius of small oligomers (r obs H Þ, using the following equation [40,51,52] r obs H ¼ r diox H � D diox D obs (1) In some cases, we observed that Aβ1-40 peptide samples showed a notable reduction in the overall rate of fibrils formation. We hypothesized that this unexpected behavior could be ascribed to small amount of Aβ1-40 fragments present in the sample and generated by peptide degradation.…”
Section: Analysis Of 26-o-acyl Iso Aβ1-40 Isomerization To Aβ1-40mentioning
confidence: 99%
“…Starting from the measured D value the apparent MW of the oligomers was calculated by the combination of Stokes À Einstein equation [34,35] with the relationship between molar radius and formula weight. [33] Assuming a spherical model, dioxane molecule radius (r H diox = 0.212 nm) was used as standard to obtain estimates of the effective hydrodynamic radius of small oligomers (r obs H Þ, using the following equation [40,51,52] r obs H ¼ r diox H � D diox D obs (1) In some cases, we observed that Aβ1-40 peptide samples showed a notable reduction in the overall rate of fibrils formation. We hypothesized that this unexpected behavior could be ascribed to small amount of Aβ1-40 fragments present in the sample and generated by peptide degradation.…”
Section: Analysis Of 26-o-acyl Iso Aβ1-40 Isomerization To Aβ1-40mentioning
confidence: 99%